Assessing the plasmonics of gold nano-triangles with higher order laser modes - Hennemann, Laura E.; Kolloch, Andreas; Kern, Andreas; Mihaljevic, Josip; Boneberg, Johannes; Leiderer, Paul; Meixner, Alfred J.; Zhang, Dai (Beilstein Journal of Nanotechnology, 2012)
Regular arrays of metallic nano-triangles – so called Fischer patterns – are fabricated by nano-sphere lithography. We studied such gold nano-triangle arrays on silicon or glass substrates. A series of different samples was investigated with a parabolic mirror based confocal microscope where the sample is scanned through the laser focus. By employing higher order laser modes (azimuthally and radially polarised laser beams), we can excite the Fischer patterns using either a pure in-plane (x,y) electric field or a strongly z-directional (optical axis of the optical microscope) electric field. We collected and evaluated the emitted luminescence and thereby investigated the respectively excited plasmonic modes. These varied considerably: firstly with the light polarisation in the focus, secondly with the aspect ratio of the triangles and thirdly with the employed substrate. Moreover, we obtained strongly enhanced Raman spectra of an adenine (sub-)monolayer on gold Fischer patterns on glass. We thus showed that gold Fischer patterns are promising surface-enhanced Raman scattering (SERS) substrates.
Keywords: Fischer pattern; higher order laser modes; localised surface plasmons; near field; surface-enhanced Raman scattering

Optical Properties of Metal Clusters - Kreibig, U.; Vollmer, M. (Springer-Verlag, 1995)

Principles of Nano-Optics - Novotny, L.; Hecht, B. (Cambridge University Press, 2006)

(untitled) - Leiderer, P.; Bartels, C.; König-Birk, J.; Mosbacher, M.; Boneberg, J. (Appl. Phys. Lett., 2004)

(untitled) - Rang, M.; Jones, A. C.; Zhou, F.; Li, Z.-Y.; Wiley, B. J.; Xia, Y.; Raschke, M. B. (Nano Lett., 2008)

(untitled) - Nelayah, J.; Kociak, M.; Stéphan, O.; Geuquet, N.; Henrard, L.; García de Abajo, F. J.; Pastoriza-Santos, I.; Liz-Marzán, L. M.; Colliex, C. (Nano Lett., 2010)

(untitled) - Geldhauser, T.; Ikegaya, S.; Kolloch, A.; Murazawa, N.; Ueno, K.; Boneberg, J.; Leiderer, P.; Scheer, E.; Misawa, H. (Plasmonics, 2011)

(untitled) - Fischer, U. C.; Zingsheim, H. P. (J. Vac. Sci. Technol., 1981)

(untitled) - Jensen, T. R.; Duval, M. L.; Kelly, K. L.; Lazarides, A. A.; Schatz, G. C.; Van Duyne, R. P. (J. Phys. Chem. B, 1999)

(untitled) - Gonçalves, M. R.; Marti, O. (New J. Phys., 2003)

(untitled) - Boneberg, J.; König-Birk, J.; Münzer, H.-J.; Leiderer, P.; Shuford, K. L.; Schatz, G. C. (Appl. Phys. A: Mater. Sci. Process., 2007)

(untitled) - Kolloch, A.; Geldhauser, T.; Ueno, K.; Misawa, H.; Boneberg, J.; Plech, A.; Leiderer, P. (Appl. Phys. A, 2011)

(untitled) - Malinsky, M. D.; Kelly, K. L.; Schatz, G. C.; Van Duyne, R. P. (J. Phys. Chem. B, 2001)

(untitled) - Félidj, N.; Aubard, J.; Lévi, G.; Krenn, J. R.; Hohenau, A.; Schider, G.; Leitner, A.; Aussenegg, F. R. (Appl. Phys. Lett., 2003)

(untitled) - Gopinath, A.; Boriskina, S. V.; Reinhard, B. M.; Dal Negro, L. (Opt. Express, 2009)

(untitled) - Chen, G.; Wang, Y.; Yang, M.; Xu, J.; Goh, S. J.; Pan, M.; Chen, H. (J. Am. Chem. Soc., 2010)

(untitled) - Haynes, C. L.; Van Duyne, R. P. (J. Phys. Chem. B, 2003)

(untitled) - Stiles, P. L.; Dieringer, J. A.; Shah, N. C.; Van Duyne, R. P. (Annu. Rev. Anal. Chem., 2008)

(untitled) - Camden, J. P.; Dieringer, J. A.; Zhao, J.; Van Duyne, R. P. (Acc. Chem. Res., 2008)

(untitled) - Jeanmaire, D. L.; Van Duyne, R. P. (J. Electroanal. Chem. Interfacial Electrochem., 1977)

(untitled) - Albrecht, M. G.; Creighton, J. A. (J. Am. Chem. Soc., 1977)

(untitled) - Sackrow, M.; Stanciu, C.; Lieb, M. A.; Meixner, A. J. (ChemPhysChem, 2008)

(untitled) - Zhang, D.; Wang, X.; Braun, K.; Egelhaaf, H.-J.; Fleischer, M.; Hennemann, L.; Hintz, H.; Stanciu, C.; Brabec, C. J.; Kern, D. P.; Meixner, A. J. (J. Raman Spectrosc., 2009)

(untitled) - Debus, C.; Lieb, M. A.; Drechsler, A.; Meixner, A. J. (J. Microsc. (Oxford, U. K.), 2003)

(untitled) - Lieb, M. A.; Meixner, A. J. (Opt. Express, 2001)

(untitled) - Taubert, R.; Hudert, F.; Bartels, A.; Merkt, F.; Habenicht, A.; Leiderer, P.; Dekorsy, T. (New J. Phys., 2007)

(untitled) - Karrai, K.; Grober, R. D. (Appl. Phys. Lett., 1995)

Handbook of Optical Constants of Solids III - Palik, E. D. (Academic Press, 1998)

(untitled) - Boyd, I. W.; Wilson, J. I. B. (J. Appl. Phys., 1982)

(untitled) - Kern, A. M.; Martin, O. J. F. (Proc. SPIE, 2009)

(untitled) - Gonçalves, M. R.; Enderle, F.; Marti, O. J. (Nanotechnology, 2012)

(untitled) - Blum, C.; Schleifenbaum, F.; Stopel, M.; Peter, S.; Sackrow, M.; Subramaniam, V.; Meixner, A. J. (Beilstein J. Nanotechnol., 2011)

(untitled) - Otto, C.; van den Tweel, T. J. J.; de Mul, F. F. M.; Greve, J. (J. Raman Spectrosc., 1986)

(untitled) - Giese, B.; McNaughton, D. (J. Phys. Chem. B, 2002)

(untitled) - Ke, W.; Zhou, D.; Wu, J.; Ji, K. (Appl. Spectrosc., 2005)

(untitled) - Bell, S. E. J.; Sirimuthu, N. M. S. (J. Am. Chem. Soc., 2006)

(untitled) - Barhoumi, A.; Zhang, D.; Tam, F.; Halas, N. J. (J. Am. Chem. Soc., 2008)

(untitled) - Lombardi, J. R.; Birke, R. L. (J. Phys. Chem. C, 2008)